استخدام تقنیة الأنفوجرافیک فى تدریس وحدة بمقرر البرمجیات بقسم المکتبات جامعة المنیا : دراسة تجریبیة - د.یارة ماهر قناوى Maher Qenawy (المجلة الدولية لعلوم المكتبات والمعلومات)
The Research Deals with the Definition and the Possibility of Infographic'sRecruitment in the Teaching Module in Software Course to Students Departmentof Libraries, Where it has an Important and Effective Role in the Transmission ofInformation , Data , and knowledge clearly and attract attention , and this is donethrough the representation of data and information visually .the study aimed to measuring the effectiveness of the use of InfographicTechnology in Teaching Module in the Software Course to Fourth Year Studentsof the Department of Libraries , The study was based on the ExperimentalMethod and the Design of Tribal and Remote Measurement of Two Groups ,One Teaching in the Traditional Way and The Other Teaching the Infographic .The study Reached Several Results the Most Important there are noStatistically Significant Differences between the Average Degree of Tribal andRemote Application in the Research Sample on their variable of the SoftwareCourse.